Effects of daily Δ9-Tetrahydrocannabinol (THC) alone or combined with cannabidiol (CBD) on cognition-based behavior and activity in adolescent nonhuman primates. (1st April 2021) - Withey, Sarah L.; Kangas, Brian D.; Charles, Sophia; Gumbert, Andrew B.; Eisold, Jessica E.; George, Susan R.; Bergman, Jack; Madras, Bertha K.
Highlights: Daily THC impaired adolescent monkey performance in a cognitive test initially, with tolerance developing to impairment. Daily THC reduced motor activity and increased sedentary behavior. Tolerance developed after weeks of daily treatment. CBD did not modulate THC effects on cognitive performance, activity or tolerance. CBD prevented THC-induced emesis on first day of daily treatment. Abstract: Background: Daily use of marijuana is rising in adolescents, along with consumption of high potency marijuana products (high % Δ-9-tetrahydrocannabinol or THC). These dual, related trends have opened gaps in understanding the long-term effects of daily consumption of a high dose of THC in adolescents and whether a therapeutic dose of cannabidiol (CBD) modulates THC effects. Methods: Adolescent squirrel monkeys ( Saimiri boliviensis ) were treated daily for four months with vehicle (n = 4), a high THC dose (1 mg/kg i.m.; n = 4), or THC + CBD (1 mg/kg +3 mg/kg i.m.; n = 4), to investigate whether: (1) a daily high THC dose affects performance in tasks of cognition (repeated acquisition, discrimination reversal); (2) a daily high THC dose affects spontaneous behavior and day/night activity (3) tolerance develops to the behavioral effects of THC; (4) whether CBD modulates THC effects. Results: THC impaired performance of adolescent monkeys in a cognitive test initially, but not performance on a task of cognitive flexibility. THC reduced motor activity and increased sedentary behavior, with tolerance developing after weeks of daily treatment. Co-administered with THC, CBD did not modulate THC effects on cognitive performance, activity or tolerance, but prevented THC-induced emesis on the first day of daily treatment. Conclusions: Daily high dosing with THC compromised performance on a task of cognition, and reduced activity in adolescent primates, with tolerance developing within weeks. Whether our observations are relevant to a broader range of cognitive tasks vital for daily function in human adolescents is uncertain.